PELAKSANAAN HUKUM WARIS ADAT DI DUSUN SUKODONO KECAMATAN TIRTOYUDO – MALANG - Taufik, Taufik; Anis, Firia (Universitas Darunnajah Jakarta, Indonesia, 2022)
The customary heir law system is one of the known and applicable heir law systems in Indonesia. This system is still widely used in some areas - which are notably Muslim-populated in Indonesia. One of them is what happened in the hamlet of Sukodono, Tirtoyudo District, Malang. The practice of inheritance distribution in this area uses the customary inheritance law system which adopts a hereditary system (parental/bilateral) drawn according to the line from the father and mother and adopts the individual inheritance system (individual). In addition, the distribution of h pound inheritance to each heir distributed evenly and fairly according to custom. In general, the settlement of inheritance distribution is done through deliberation between families by presenting customary figures or community figures. It is intended that in the event of a dispute between the heirs then be solved by mixing the hands of traditional leaders and resolved amicably.